Too much of a good thing? Hand hygiene and the long-term course of contamination-related obsessive-compulsive symptoms - Jelinek, Lena; Göritz, Anja S.; Miegel, Franziska; Schuurmans, Lea; Moritz, Steffen; Yassari, Amir H.; Müller, Jana Christina (Frontiers in Psychology, 2024)
Increased hygiene behavior may be a factor in the development of contamination-related obsessive-compulsive symptoms (C-OCS). We aimed at investigating (1) the course of C-OCS over 1 year after the start of the COVID-19 pandemic and (2) the effects of changes in hand hygiene (i.e., duration and frequency of handwashing) and related distress regulation on the long-term course of C-OCS. In a longitudinal study, we assessed 1,220 individuals from the German general population at the start of the COVID-19 pandemic (t1), 3 months later (t2), and 12 months later (t3). Prepandemic data were available in a subsample from 2014 (n = 430). A decrease in C-OCS over the first year of the pandemic emerged with a small effect size. Thirty-six percent of the participants scored above the clinical cut-off score at t1, 31% at t2, and 27% at t3. In 2014, only 11% scored above the clinical cut-off score. Hierarchical regression showed that C-OCS at t1 was the strongest predictor of a long-term increase in C-OCS. With small effect sizes, change in the duration (not frequency) of handwashing from t1 to t2, as well as the distress-reducing effect of handwashing served as additional predictors. Implications for information on hand hygiene guidelines are discussed.